2014
DOI: 10.11648/j.ajhr.20140202.18
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Sexual Risk Behaviours of In-School Youth: Effect of Living Arrangement of Students; West Gojam Zone, Amhara Regional State, Ethiopia

Abstract: Abstract:Background: Contemporary threats to adolescents' health are primarily the consequence of risk behaviors and their related adverse outcomes. Identifying factors associated with adolescents' risk behaviors is critical for developing effective prevention strategies. A number of risk factors have been identified, including familial environment; however, to the investigator's best knowledge, there have been only one previous study of possible differential vulnerabilities of in-school adolescents to risky s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 11 publications
5
12
2
Order By: Relevance
“…This finding was in line with other previous studies [34, 35]. This might be due to the fact that such students were at higher probability of sharing information regarding their day to day life and in a position to conform to peers’ informal rules.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was in line with other previous studies [34, 35]. This might be due to the fact that such students were at higher probability of sharing information regarding their day to day life and in a position to conform to peers’ informal rules.…”
Section: Discussionsupporting
confidence: 93%
“…This was in agreement with findings from previous literatures. The possible explanation could be the fact that as age increases, involving in sexual practice increases due to the social acceptance of sexual intercourse in late age [12, 18, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…The sample size was determined using single population proportion formula with the following assumption; p= 14% 16 and margin of error 5%. The final sample size was 288 in-school youths living with their parents.…”
Section: Sample Size Determinationmentioning
confidence: 99%
“…in Ethiopia indicated that majority of youths are in-schools and living arrangement of high school students are living with friends followed by relatives and both biological parents 15 . For urban students, the most common living arrangements were living with both parents or with one biological parent 5,7,15,16 . Though there are a number of factors affecting the sexual health of in-school youths, Family connectedness and living arrangements seem an important factor affecting the sexual decisions of youths.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies (Resnick, 1997;Asrat, 2014) are also confirming incidences of secondary school students becoming sexually active at an increasing earlier age.…”
Section: Students' Engagement In Sexual Intercoursementioning
confidence: 67%